2022
DOI: 10.1002/jha2.534
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of poor peripheral blood stem cell mobilizers with multiple myeloma at the first mobilization: A multicenter retrospective study in Japan

Abstract: Autologous stem cell transplantation (ASCT) remains an important therapeutic strategy for multiple myeloma; however, a proportion of patients fail to mobilize a sufficient number of peripheral blood stem cells (PBSCs) to proceed to ASCT. In the present study, we aimed to clarify the characteristics and outcomes of poor mobilizers. Clinical data on poorly mobilized patients who underwent PBSC harvest for almost 10 years were retrospectively collected from 44 institutions in the Japanese Society of Myeloma (JSM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Herein, although a sufficient number of CD34þ hematopoietic stem cells were collected, the megakaryocytic hematopoietic reconstruction was delayed due to impaired megakaryocytic generation ability. 19 thrombopoietin (TPO) receptor agonists can increase PLT number in patients with primary immune thrombocytopenia and aplastic anemia by promoting the maturation of the megakaryocytic system. Besides, TPO receptor agonists are widely used for poor PLT engraftment after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, although a sufficient number of CD34þ hematopoietic stem cells were collected, the megakaryocytic hematopoietic reconstruction was delayed due to impaired megakaryocytic generation ability. 19 thrombopoietin (TPO) receptor agonists can increase PLT number in patients with primary immune thrombocytopenia and aplastic anemia by promoting the maturation of the megakaryocytic system. Besides, TPO receptor agonists are widely used for poor PLT engraftment after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, although a sufficient number of CD34+ hematopoietic stem cells were collected, the megakaryocytic hematopoietic reconstruction was delayed due to impaired megakaryocytic generation ability. 19 …”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, previously, it was demonstrated that the outcome after ASCT was poorer if lower amounts of stem cells were harvested. 15 Therefore, the best preharvest assessment of the stem cell count is needed to optimize the stem cell harvest and maximize the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Preceding studies examining the performance of automated PBSC measurement showed a significant correlation to flow cytometric measurement consequently proposing XN-20 as a possible surrogate marker for initiation of the apheresis procedure. 7,8,10,11,[15][16][17][18][19][20][21] Although, it needs to be mentioned that some point out the diagnostic accuracy in the clinical decision range might be limited. 8 Furthermore, depending on the utilized analyzer the diagnostic accuracy may be confined.…”
Section: Discussionmentioning
confidence: 99%
“…When sufficient CD34 + cells cannot be collected, the patient must either undergo re-harvest or be treated with other options. These cause inconvenience and sometimes worsen clinical outcomes [8][9][10][11]. Previous studies have reported various factors associated with mobilization failure, and some researchers have developed methods to predict CD34 + cell collection yield [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%